Obesity in Uruguay. It´s time to act - Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2024)
Editorial on the situation of the topic Obesity in Uruguay.Obesity is a chronic, progressive and multifactorial disease, its origin involves genetic factors, poor metabolic adaptation, neuroendocrine alterations, important changes in lifestyle, food composition and social inequality, among others.